The effect of integration between audit and leadership on supply chain performance: evidence from UK based supply chain companies - Ul-Hameed, Waseem; Mohammad, Hisham; Kadir Shahar, Hanita; Aljumah, Ahmad Ibrahim; Azizan, Syafiqah (2019)
Supply chain performance has been a key element of competitive strategy to boost organizational productivity and profitability. In the United Kingdom (UK), a survey disclosed that approximately 40% of the UK’s gross domestic product (GDP) was consumed on supply chain related activities. Because of the extensive use of gross domestic product (GDP) on supply chain, it is important to work on UK based supply chain companies and to reveal various factors to enhance supply chain performance. Therefore, the primary objective of the current study is to investigate the combine effect of audit determinants and leadership styles to enhance supply chain performance in UK based companies. Data were collected from audit department employees and other managerial employees who are closely related to supply chain activities. After analyzing the data through Smart PLS 3, it was found that audit and leadership styles played important contribution in supply chain performance. Moreover, top management and employee commitment to change maintained significant influence to enhance positive effect on audit and leadership. This study is much significant for UK supply chain companies to enhance supply chain performance.